2018
DOI: 10.5194/acp-18-14965-2018
|View full text |Cite
|
Sign up to set email alerts
|

The quasi-liquid layer of ice revisited: the role of temperature gradients and tip chemistry in AFM studies

Abstract: Abstract. In this work, we present new results of atomic force microscopy (AFM) force curves over pure ice at different temperatures, performed with two different environmental chambers and different kinds of AFM tips. Our results provide insight to resolve the controversy on the interpretation of experimental AFM curves on the ice–air interface for determining the thickness of the quasi-liquid layer (QLL). The use of a Mini Environmental Chamber (mEC) that provides an accurate control of the temperature and h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 39 publications
6
30
0
Order By: Relevance
“…The interfacial tension between ice and vapour is not well known. Following previous studies, we assume a quasi-liquid layer to form on the ice surface (Gelman Constantin et al, 2018;Wettlaufer, 1999). Then an upper limit of the interfacial tension of ice and water vapour is given by the sum of the interfacial tensions of water and vapour and ice and water: γvi(T) = γvw(T) + γiw(T), following David et al (2019).…”
mentioning
confidence: 99%
“…The interfacial tension between ice and vapour is not well known. Following previous studies, we assume a quasi-liquid layer to form on the ice surface (Gelman Constantin et al, 2018;Wettlaufer, 1999). Then an upper limit of the interfacial tension of ice and water vapour is given by the sum of the interfacial tensions of water and vapour and ice and water: γvi(T) = γvw(T) + γiw(T), following David et al (2019).…”
mentioning
confidence: 99%
“…The humidity uncertainty is quite large, as expected, considering that we are measuring very low vapor pressures at the analyzed temperature range. However, some results obtained in a previous study 17 showed that during ice deposition at constant temperature, RH attained a constant value of (102.5 ± 4.4)%, indicating that probably the uncertainty in the RH is overestimated. Table II summarizes the sample temperature, supercooling, and temperature and RH of the humid nitrogen above the sample for the experiments performed.…”
Section: Resultsmentioning
confidence: 85%
“…AFM force curves over ice are usually used to study the thickness of the quasi-liquid layer (QLL) that exists over a supercooled ice surface and whose properties differ from those of the bulk supercooled liquid at the same temperature. [13][14][15][16][17] When the tip is away from the ice surface, the force between the tip and the sample is zero. At a certain point, close to the surface, the tip experiences an attractive force, jumping into the ice.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…One of the plausible causes for the considerable variations of the uptake amounts is the presence/absence of thin liquid water layers, so called quasi-liquid layers (QLLs), on ice crystal surfaces at temperatures below the melting point [8][9][10][11]. In the case of nitric acid (HNO 3 ) gas, heterogeneous…”
Section: Introductionmentioning
confidence: 99%